Laser-induced enhancement of tunneling in NHD2 - Sala, Matthieu; Meyer, Hans-Dieter (The journal of chemical physics, 2012)
We apply and explore techniques aiming at enhancing the tunneling by laser fields, originally developed for a one-dimensional model, to a complete six-dimensional vibrational model of the inversion motion in NHD2. The computational study is performed with the multi-configuration time-dependent Hartree method. Assuming an ideal three-dimensional alignment we obtain a driven tunneling time twenty times smaller than the natural one, in rather good agreement with an oversimplified three-state model. In the case of one-dimensional alignment, a linearly polarized field leads to a poor enhancement of the tunneling probability, after averaging over the rotation about the alignment axis, whereas a circularly polarized field improves the rotationally averaged tunneling probability at the end of the pulse.
Published online 21 May 2012
Gesehen am 19.06.2018